PENGEMBANGAN E-MODULBERBASIS PENDEKATAN SAINTIFIK PADA MATERI FUNGSI EKSPONENSIAL DAN LOGARITMA UNTUK KELAS X SMA/MA - Aisyah Amini (Departemen Matematika, 2022)
The fact that the obstacles felt by students in understanding mathematics learning material during blended learning is the background of this research. In addition, technological developments that encourage convenience in almost all areas of life, including education. The 2013 curriculum directs students to take lessons and dominate teaching and learning activities with a scientific approach can also be developed in accordance with existing technological developments. The research is aimed at developing an e-module based on a scientific approach on the material of exponential and logarithmic functions for students of class X SMA/MA which is valid and practical. The e-module that has been developed is validated by experts first, then the e-module is tested at SMA N 1 Padangpanjang. The results obtained in this study are e-modules based on a scientific approach which were developed to meet the very valid and very practical categories. Keywords– E-modul, scientific approach, exponential and logarithmic function